Characterization of Deep-Water Submarine Fan Reservoir Architecture: AB120 Reservoir in the Campos Basin - Zhao, Chen; Hu, Xiuquan; Li, Jianghan; Yi, Chi; Li, Jieyi; Niu, Zhipeng (Frontiers in Earth Science, 2022)
The exploration of deep-water submarine-fan reservoirs has become a prominent research area for hydrocarbon discovery and recovery. However, the high operational costs render efficient exploration of this type of reservoir an imperative and urgent undertaking, and the pivotal foundation lies in studying reservoir architectures. This work, presents a case study of the deep-water submarine fans in the Albacora Leste oilfield in Brazil, carried out a study on the characterization of the underground reservoir architecture based on well-log and seismic model fitting by systematically establishing a sedimentary microfacies distribution model for each reservoir based on detailed stratigraphic framework with the well seismic joint characterization method and various types of data (e.g., geological, well-log, and seismic data). The results are as follows: The sedimentary microfacies of the deep-water submarine fans in the study area can be subdivided into tongue-shaped-lobe, muddy-channel, sandy-channel, and contourite deposits. Due to a data abundance and quality constraints, the architecture of the target layer in the study area is characterized based on level 4 architectural elements. The AB120 reservoir consists of three complex channels (I, II, and III) and two tongue-shaped complex lobes (I and II). Complex channels I and III were the first and last to be deposited, respectively, and complex lobe I was deposited earlier than complex lobe II. Complex channels II and III supplied complex lobes I and II, respectively. Vertically, complex lobe II is composed of three single lobes formed at different stages, the youngest of which is distributed over the largest area. Complex lobe II has already been drilled and is currently undergoing development. However, complex lobe I has not been developed yet. This study has both great practical significance for the effective development of deep-water submarine-fan reservoirs in this area and considerable theoretical significance for the advancement of deep-water sedimentology.